Simulation Research of LDPC Coding Schemes in Satellite Communication with SC-FDMA - Hua, Nengtang; Wang, Jie; Chen, Ming; Zhou, Ke; Song, Huilin (IEEE Vehicular Technology Conference, 2024)
Single Carrier Frequency Division Multiple Access (SC-FDMA) is a promising technology for uplink communication in satellite communication systems due to its advantages such as low peak-to-average ratio, high spectral efficiency, and flexible resource allocation. This paper designs a physical layer model for the satellite communication return link with SC-FDMA modulation. Based on an established satellite return link, we employ a localized FDMA (L-FDMA) subcarrier mapping scheme to compare the burst error rate (BER) simulation performance of three coding schemes: New Radio (NR) LDPC, Wireless Local Area Network (WLAN) LDPC, and Digital Video Broadcasting - Satellite - Second Generation (DVB-S2) LDPC. The simulation results propose that the NR LDPC coding scheme has better BER performance compared to the other two LDPC coding schemes, and the NR LDPC coding scheme is more suitable for satellite burst communication.